PERUBAHAN BEBERAPA SIFAT KIMIA TANAH PESISIR DAN PENGARUHNYA TERHADAP PERTUMBUHAN CABAI RAWIT (Capsicum frutescens L.) YANG DIBERI ABU SEKAM PADI DAN PUPUK NPK - Tyas, Sela Arning; Ginting, Sahta; Anas, Arsy Aysyah; Darwis, Darwis; Pasolon, Yulius Barra; Namriah, Namriah (Jurnal Agroteknologi (Agronu), 2023)
Beach sandy land has great potential to be used as an agricultural area, because it has a very large area and has not been utilized optimally, especially as a cultivation area. The aims of this study were: To determine the effect of rice husk ash and NPK fertilizer on changes in some of the chemical properties of coastal soils and the growth of cayenne pepper plants. To determine the interaction effect of rice husk ash and NPK fertilizer on changes in several chemical properties of coastal soils and the growth of cayenne pepper plants. This research was conducted at Field Laboratory II, Faculty of Agriculture, University of Halu Oleo. Analysis of soil samples was carried out at the Testing Laboratory of the Department of Soil Science, Faculty of Agriculture, Halu Oleo University. This research was conducted from August 2022 to October 2022. This research used a Randomized Block Design (RBD) consisting of A0 = 0 g polybag-1, A1 = 25 g polybag-1 or equivalent to 5 ton ha-1, A2 = 37, 5 g polybag-1 or the equivalent of 7.5 tons ha-1, B0 = 0 g polybag-1, B1 = 5 g polybag-1 or the equivalent of 1 ton ha-1, B2 = 7.5 g polybag-1 or equivalent to 1.5 tons ha-1. The variables observed included analysis of soil chemical properties and plant growth. The results showed that a mixture of rice husk ash and NPK fertilizer was able to increase the nutrient content of N, P, K, pH, C-Organic in coastal soil, characterized by an increase in plant height and number of leaves of red chili plants and the dose of organic fertilizer that had the best effect, namely 37.5g and 7.5g.Keywords: husk ash, C-organics, soil chemical, sand land, NPK